HotSpots and Trends in Spatial Research on Historic Neighborhoods in China: Based on CiteSpace Visual Knowledge Graph Analysis - Zha, Danni (International Journal of Social Sciences and Public Administration, 2025)
Historic districts are the carriers of urban memory, which not only carry rich historical and cultural information, but also are an important manifestation of national identity and cultural diversity. In recent years, the spatial research of China's historic districts has gradually become a hotspot of academic attention. In order to explore the hotspots and trends of the spatial research of China's historic districts, this paper takes the literature included in the China Knowledge Network from 2004 to 2024 as the data base, searches with the keywords of "historic districts" and "space", and conducts visualization and analysis by using the CiteSpace software was used for visualization and analysis. It is found that: ①The annual publication volume of the research on the space of historic districts in the past two decades shows the characteristics of rising and fluctuating, and the research institutions are mainly concentrated in colleges and universities. ②In terms of research stages, it has mainly experienced three stages: the starting stage, the emergence of new research trends and directions, and the people-oriented stage. ③There is a lack of comparative analysis of research objects and fewer quantitative research methods. Based on this, this paper puts forward the research outlook, with a view to providing certain reference and reference for the spatial research of historical neighborhoods through the research results of this paper.